2007
DOI: 10.1038/sj.emboj.7601482
|View full text |Cite
|
Sign up to set email alerts
|

Reversible movement of switch 1 loop of myosin determines actin interaction

Abstract: The conserved switch 1 loop of P-loop NTPases is implicated as a central element that transmits information between the nucleotide-binding pocket and the binding site of the partner proteins. Recent structural studies have identified two states of switch 1 in G-proteins and myosin, but their role in the transduction mechanism has yet to be clarified. Single tryptophan residues were introduced into the switch 1 region of myosin II motor domain and studied by rapid reaction methods. We found that in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 31 publications
10
68
0
Order By: Relevance
“…(ii) The present calculations are also supported by data from Kintses et al (22), who had shown that the light scattering signal changes from actin dissociation covary with the signals from switch-1 closing (fluorescence of W239 þ ). This observation suggests that the u50 domain and switch 1 move simultaneously, consistent with the present observation that they belong to the same semirigid unit.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…(ii) The present calculations are also supported by data from Kintses et al (22), who had shown that the light scattering signal changes from actin dissociation covary with the signals from switch-1 closing (fluorescence of W239 þ ). This observation suggests that the u50 domain and switch 1 move simultaneously, consistent with the present observation that they belong to the same semirigid unit.…”
Section: Discussionsupporting
confidence: 77%
“…This setup has been described previously in detail by Koppole et al (19) Molecular Kinematics. The timescale of the ATP-induced dissociation of rigor myosin from actin is in the millisecond range (5,22), beyond the scope of unconstrained molecular dynamics simulations. Applying constraints along some predefined reaction coordinate to accelerate the simulation tends to favor events correlating strongly with this predefined reaction coordinate, thus biasing the sequence of events upon which a description of the mechanism is to be based (33).…”
Section: Methodsmentioning
confidence: 99%
“…We show for the first time an actin-dependent closure of switch I in the ADP state that has only been observed in smooth muscle myosin to date, because actin has been shown to open switch I in skeletal and Dictyostelium discoideum myosin where it has been studied previously (19,40). Although it is unclear how actin binding causes closure of switch I, this conformation is most likely stablilized by the specific binding between actin and smooth muscle myosin.…”
Section: Discussionmentioning
confidence: 92%
“…The two states showed a temperature-dependent equilibrium between them, favoring the closed conformation of the active site at lower temperatures. There is also kinetic evidence from different myosin isoforms, indicating the presence of multiple actomyosin-ADP states (17)(18)(19)(20). In smooth muscle myosin, strong binding to both actin and ADP has been proposed to be necessary for the formation of the latch state, where a decrease in regulatory light chain phosphorylation leads to maintained tension for long periods of time with little hydrolysis of ATP (21) and which may be related to the closed active site state previously observed at low temperature by EPR and transient kinetics (16 -19).…”
mentioning
confidence: 99%
“…Specifically, how tightly coupled is the communication pathway from the actin interface to the nucleotide pocket or to the force-generating domain? There is evidence for coupling between the actin-binding cleft and nucleotide pocket (63)(64)(65), as well as between the nucleotide pocket and the force-generating domain (66,67). Recent work suggests that there is direct coupling between the actin-binding interface, particularly the myosin activation loop, and the relay helix in the myosin force-generating domain (68).…”
Section: Discussionmentioning
confidence: 99%